ANALISIS PROSEDUR PENGELOLAAN SURAT KELUAR PADA BAGIAN UMUM DI KANTOR IMIGRASI KELAS 1 BANDUNG - Delia Subrayanti; Shiva Cherolina; Muhamad Amin Ma'ruf Aqilludin (Jurnal Administrasi Perkantoran dan Kesekretariatan, 2022)
This study aims to determine the procedures for managing outgoing mail in the General Section of the Immigration Office Class I Bandung. This research is a descriptive research with qualitative method. Data collection techniques used: observation, interviews, and documentation. The results of this study are the procedures for managing outgoing letters are quite good starting from Concept Making, Concept Approval, Concept Typing, Letter Numbering, Letter Signing, Stamping, Recording Outgoing Letters in the Outgoing Mail Agenda Book, Sending letters is done in two ways, namely through employees in the General Section of the Immigration Office Class 1 Bandung and mail delivery services. Constraints in managing outgoing mail in the General Section of the Immigration Office Class 1 Bandung are lacking human resources to manage administrative activities such as letters often causing problems because work activities are hampered. Administrative employees cannot always be in place because they have other tasks to do, sometimes administrative employees are not careful in providing letter numbers so that the same letter numbers are still found. Facilities in supporting the management of outgoing mail at the Class 1 Bandung Immigration Office manually, namely the use of the agenda book system is not in accordance with what is in theory because there are still some differences. From these results, it is necessary to immediately add employees to handle office administrative activities, one of which is the management of outgoing mail in the General Section of the Class 1 Immigration Office in Bandung in order to support the smooth running of all work activities and to streamline working hours. The facilities in supporting the management of outgoing mail in the General Section of the Class 1 Immigration Office in Bandung are not good enough because there are still some facilities that are not yet available and some of the facilities are still inadequate. The author suggests to the Immigration Office Class 1 Bandung to immediately provide less facilities such as the addition of a Filling Cabinet or File Cabinet, Guide and Folder for the management and storage of letters or documents that are more appropriate so that there is no excessive accumulation of documents and hampers the work process. and reduce the aesthetic value in the workspace.